Legislative analysis of the circular paradigm economy - Porcelli, Adriana Margarita (2019)
The currently prominent economic model is based on obtaining economic growth through optimal use of inputs and factors of production, the use of fossil fuels and accelerated extraction of natural resources. In recent decades, this model has caused the depletion of natural resources and the widespread degradation and damage to ecosystems, which has given rise to an alternative economic model called “the green economy” and within it the closed-cycle circular economy. The objective of this paper is to analyze whether the circular economy is a reliable and plausible alternative to mitigate the effects of an economic model in crisis and to promote a highly sustainable culture and its reception in different legislations. The methodology adopted is related to documentary observation, the survey, revision and systematization of the existing bibliography on the subject, the identification of specific theoretical-technical concepts and principles and the analysis of the legislations that received this new economy. Finally, to sum up, there is a worldwide concern regarding environmental deterioration, and there is some progress in creating a regulatory framework, both at the national, regional and international levels, in order to promote circularity.